Crosstalk Spectrum Predictions Considering Frequency-Dependent Parameters in Electric Vehicles - Guo, Yanjie; Wang, Lifang; Liao, Chenglin (Applied Computational Electromagnetics Society Journal (ACES), 2021)
This paper presents a method which combines impedance measurements, calculations, and equivalent model together to predict crosstalk spectrums. It is simple for calculation and also has good accuracy, because frequency-dependent parameters of both cables and terminal loads are considered. So it has advantages in some complex situations such as electric vehicle (EV). Firstly, a model of single line and twisted-pair wires is established to describe the crosstalk system. In this model, crosstalk voltage expressions are given, and frequency-dependent parameters are obtained from impedance measurements and calculations. Then in order to verify the method, crosstalk spectrums are predicted under conditions of resistance load and frequency-dependent load. Furthermore, predictions and experiments are compared to assess the effectiveness of the method. Based on the predicted and experimental results, frequency domain characteristics of crosstalk are discussed and influence factors are analyzed.